PREVALENSI GLAUKOMA SUDUT TERBUKA PRIMER DI RSUP SANGLAH PERIODE JUNI 2017 – JUNI 2018 - Gde Aditya Putra Deva; Ni Made Ari Suryathi; I Made Agus Kusumadjaja (E-Jurnal Medika Udayana, 2020)
ABSTRACT Primary Open Angle Glaucoma (POAG) is often referred to as "the silent thief of sight" because of an increase in intraocular pressure in patients with POAG is not accompanied by any symptoms (asymptomatic). Quite a lot of people in Bali aged > 40 years, which is one of the risk factors of POAG. Seeing this, the researchers wanted to study the prevalence of POAG at Sanglah Hospital in the period June 2017 - June 2018. The aim of this study is to describe the prevalence of primary open angle glaucoma (POAG) at Sanglah Hospital period June 2017 - June 2018. This study used cross-sectional descriptive study design. The subjects were 56 patients with POAG at Sanglah Hospital period June 2017 - June 2018. Data were collected in July until August 2018 The research data was secondary data obtained from the patient's medical record. The results showed that the prevalence of primary open-angle glaucoma at Sanglah Hospital period June 2017 - June 2018 most often found in the age group 50-59 years (44.6%) greater proportion in male (60.7%), the region with the highest number of POAG was in Denpasar POAG ( 44.6%), did not have a family history (98.2%), has a value of intraocular pressure > 21 mm Hg (60.7%), and most are treated with medical treatment and surgery (53.6%). Keywords: Primary Open Angle Glaucoma, Optic Neuropathy, Intraocular Pressure, Risk Factor